2020
DOI: 10.1177/2331216520916682
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Influence of Head Movement on Hearing Aid Algorithm Performance Using Acoustic Simulations

Abstract: Head movements can improve sound localization performance and speech intelligibility in acoustic environments with spatially distributed sources. However, they can affect the performance of hearing aid algorithms, when adaptive algorithms have to adjust to changes in the acoustic scene caused by head movement (the so-called maladaptation effect) or when directional algorithms are not facing in the optimal direction because the head has moved away (the so-called misalignment effect). In this article, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…Moreover, when moving the head, adaptive beamformers need time to adjust to the new target direction. Hendrikse et al. (2020) found this effect of algorithm adaptation to be less than 1 dB in realistic everyday scenarios comparable to ours.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, when moving the head, adaptive beamformers need time to adjust to the new target direction. Hendrikse et al. (2020) found this effect of algorithm adaptation to be less than 1 dB in realistic everyday scenarios comparable to ours.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, in more realistic acoustic environments, Grange and Culling (2016) have shown that even small amounts of head orientation differences can result in considerable SNR changes at the hearing device's microphones. Moreover, Hendrikse et al (2020) investigated the effect of head movements on algorithm benefit in various spatial acoustic scenarios, and they found a significant detrimental effect on the benefit provided by adaptive beamformers. Consequently, the influence of the subject's head orientation and movement on the beamformers' benefits reported by free-field studies cannot be ruled out.…”
mentioning
confidence: 99%
“…In that case, subjects virtually stopped moving their heads. Because head movement reduces the benefit in signal to noise ratio provided by spatial filtering ( Hendrikse et al 2020 ), realistic head movement may be a crucial factor in ecologically more valid hearing aid evaluation in the lab.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…The proposed approach can be illustrated by the example of head movements that typically occur in acoustic communication conditions. Hendrikse et al (2020) found in the virtual reality lab that individual head-movement tracks recorded in turn-taking conversations ( Hendrikse et al 2019 ) differentially affected the benefit in signal to noise ratio provided by a standard adaptive directional microphone and that head movement significantly reduced signal to noise ratio benefit of the adaptive directional microphone on average. This demonstrates the relevance of realistic head movement for ensuring the ecological validity of hearing aid outcome measures (benefit in signal to noise ratio, in this case).…”
Section: Requirements For Reflecting Real-life Communication In the Lmentioning
confidence: 99%
See 1 more Smart Citation